CLIMATE VARIABILITY AND ITS IMPACT ON CENDRAWASIH BIRDS IN THE YAPEN ISLANDS - Krisson Raunsay, Edoward; David Reinhard Jesajas; Dolfina Costansah Koirewoa; Ortis Fredi Waromi (International Journal of Multidisciplinary Reseach, 2026)
Climate variability is one of the environmental factors that influences the dynamics of tropical forest ecosystems and the sustainability of their biodiversity. The Yapen Islands, as part of the Papua region, have a tropical forest ecosystem that serves as an important habitat for birds of paradise, an endemic bird species with high ecological and conservation value. This study aims to analyze the effect of climate variability on the habitat and ecological dynamics of birds of paradise in the Yapen Islands. The study used a literature review method by examining various scientific articles obtained from international academic databases through a systematic selection process. The analysis was conducted on relevant literature to identify patterns of relationships between climate change, tropical forest ecosystem dynamics, and the sustainability of bird-of-paradise populations. The results show that climate variability, especially changes in temperature and rainfall patterns, contributes to changes in forest vegetation structure, food source availability, and reproductive patterns of birds of paradise. These changes have the potential to affect habitat distribution and long-term population stability of this species. The study's conclusions emphasize that understanding the relationship between climate variability and the ecological dynamics of birds of paradise is crucial in supporting ecosystem-based conservation strategies and climate change adaptation in the Papua region.